The effect of dopamine agonist therapy on large functionless pituitary tumours. - Grossman, A; Ross, R; Charlesworth, M; Adams, C; Wass, J; Doniach, I; Besser, G (1985)
Fifteen patients (12 male) with large pituitary tumours and serum prolactin levels below 1000 mU/l were given dopamine agonist therapy (bromocriptine, mesulergine or pergolide) for a mean of 9 months (range 3-36 months). Serum prolactin became undetectable in all. Despite this, significant suprasellar extensions and any associated neurological defect remained in 14 patients, who therefore were referred for surgery. In one patient there was evidence of spontaneous pituitary infarction unrelated to dopamine agonist therapy. At operation 12 patients had apparently functionless pituitary adenomas which failed to immunostain for prolactin, one had an epidermoid cyst and one a Rathke's pouch cyst. We conclude that patients with large pituitary tumours and only a mildly elevated serum prolactin are unlikely to have prolactinomas, and that such tumours are not likely to show significant tumour shrinkage with medical treatment with dopamine agonists.